THE SLOW APPROACH: Mozambique’s contribution to Operation Zimbabwe and the new basis for relations with the West. - BUSSOTTI, LUCA (Outros Tempos: Pesquisa em Foco - História, 2024)
During the Cold War years, shortly after gaining its independence, socialist Mozambique was faced with a very thorny issue: that of the sabotage carried out by Ian Smith's Rhodesia on Mozambican territory, with disastrous consequences for the security of Mozambique. This study, based on a political history perspective, was conducted using an approach based in the discourse analysis of American documents that can be consulted today in public archives, starting from those of the State Department and of the Central Intelligence Agency (CIA). The research concluded that Samora Machel emerged as a protagonist in the transition from Rhodesia to Zimbabwe, partly breaking away from their closeness to the Socialist bloc and approaching the Anglo-American bloc to defend specific national interests. This attitude shows how, in the broad world geopolitics, even small countries like Mozambique can play leading roles, going beyond ideological blocs that seemed insurmountable.